Pengaruh Internal Audit Dan Penerapan Good Corporate Governance Dalam Meningkatkan Pengendalian Intern Piutang Di PT. Enseval Putera Megatrading Tbk. Cabang Bogor - Harnavela Sofyan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This research has done to know how: (1) Internal Audit, Implementation Good Corporate Governance and accounts receivable internal control at Branch office Bogor PT. Enseval Putera Megatrading Tbk. (2) Effect of Internal Audit and Implementation of Good Corporate governance silmultaneously and partially on the accounts receivable internal control at Branch office Bogor PT. Enseval Putera Megatrading Tbk. (3) Effect of Internal Audit and the Implementation of Good Corporate Governance in improving the accounts receivable internal control at Branch office Bogor PT. Enseval Putera Megatrading Tbk. The method used is descriptive method analisys the survey approach. The analisys tools is the analisys of the path (path analisys) with the ordinal measurement scale. Partial hypothesis testing using t test and simultaneously by using the F test with the significant level (α=0,05). (1) internal audit, implementation Good Corporate Governance and the accounts receivable internal control at Branch office Bogor PT. Enseval Putera Megatrading Tbk has been properly implemented (2) The analisys using path analisys, internal audit have effect of the implementation good corporate governance. (3) testing simultaneously or partially showed that, the internal audit and the implementation Good Corporate Governance simultaneously and partially significant effect on accounts receivable internal control.